A data-driven two-stage maintenance framework for degradation prediction in semiconductor manufacturing industries. (July 2015) - Luo, Ming; Yan, Heng-Chao; Hu, Bin; Zhou, Jun-Hong; Pang, Chee Khiang
Graphical abstract: Highlights: A two-stage maintenance framework predicts degradation in semiconductor industries. Multiple regression forecasting investigates the linear characteristics of system. Genetic algorithm overcomes the bottleneck of local optimality in neural networks. Secondary block (SB) as a backup achieves the highest prediction accuracy of 74.1%. SB addresses non-stationary processes with complex statistics and imbalanced data. Abstract: To reduce the production costs and breakdown risks in industrial manufacturing systems, condition-based maintenance has been actively pursued for prediction of equipment degradation and optimization of maintenance schedules. In this paper, a two-stage maintenance framework using data-driven techniques under two training types will be developed to predict the degradation status in industrial applications. The proposed framework consists of three main blocks, namely, Primary Maintenance Block (PMB), Secondary Maintenance Block (SMB), and degradation status determination block. As the popular methods with deterministic training, back-propagation Neural Network (NN) and evolvable NN are employed in PMB for the degradation prediction. Another two data-driven methods with probabilistic training, namely, restricted Boltzmann machine and deep belief network are applied in SMB as the backup of PMB to model non-stationary processes with the complicated underlying characteristics. Finally, the multiple regression forecasting is adopted in both blocks to check prediction accuracies. The effectiveness of our proposed two-stage maintenance framework is testified with extensive computation and experimental studies on an industrial case of the wafer fabrication plant in semiconductor manufactories, achieving up to 74.1% in testing accuracies for equipment degradation prediction.